Bearing witness: United States and Canadian maternity support workers' observations of disrespectful care in childbirth. Issue 3 (30th July 2018) - Morton, Christine H.; Henley, Megan M.; Seacrist, Marla; Roth, Louise Marie
Abstract: Background: Disrespectful care and abuse during childbirth are acknowledged global indicators of poor quality care. This study aimed to compare birth doulas' and labor and delivery nurses' reports of witnessing disrespectful care in the United States and Canada. Methods: Maternity Support Survey data (2781 respondents) were used to investigate doulas' and nurses' reports of witnessing six types of disrespectful care. Multivariate analysis was conducted to examine the effects of demographics, practice characteristics, region, and hospital policies on witnessing disrespectful care. Results: Nearly two‐thirds of respondents reported witnessing providers occasionally or often engaging in procedures without giving a woman time or option to consider them. One‐fifth reported witnessing providers occasionally or often engaging in procedures explicitly against the patient's wishes, and nurses were more likely to report witnessing this than doulas. Doulas and nurses who expected to leave their job within three years were significantly more likely to report that they witness most types of disrespectful care occasionally or often (OR 1.78‐2.43). Conclusions: Doulas and nurses frequently said that they witnessed verbal abuse in the form of threats to the baby's life unless the woman agreed to a procedure, and failure to provide informed consent. Reports of witnessing some types of disrespectful care in childbirth were relatively uncommon among respondents, but witnessing disrespectful care was associated with an increased likelihood to leave maternity support work within three years, raising implications for the sustainability of doula practice, nursing work force shortages, and quality of maternity care overall.